Analysis of pit and score tooth-mark sizes from bones modified by Holocene Australian terrestrial fauna in relation to body size. (August 2018) - Koungoulos, Loukas; Faulkner, Patrick; Asmussen, Brit
Abstract: Carnivorous mammals, particularly the Tasmanian devil ( Sarcophilus harrisii ), dingo ( Canis dingo ), and tiger quoll ( Dasyurus maculatus ) have been implicated by previous research as having affected Australian faunal assemblages through deposition or modification of skeletal materials. One way of identifying such taphonomic agency is through the examination of tooth-marks left behind by modern feeding carnivores and comparing them to analogous archaeological materials. Overseas research has compared the tooth-marks of several relevant taxa through captive feeding experiments, focusing on the sizes of pits and scores and their relation to body size. Due to highly variable sampling approaches and limited reporting of mark sizes a similar multi-species comparison has not been feasible in Australia. To address this, experimental feeding trials were carried out with captive Tasmanian devils, dingoes, tiger quolls, eastern quolls, lace monitors, dogs, and one of the authors. Analysis of 2895 tooth-marks revealed that considerable overlap exists between the sizes of pits and scores from the aforementioned three species. The only species that could be consistently differentiated from the rest were the taphonomically insignificant lace monitor and eastern quoll. The ability of Tasmanian devil and tiger quoll to produce very large tooth-marks in proportion to their small body size means that Australian fauna do not conform to trends observed in overseas studies where tooth-marks separate into categories that broadly correspond with body weight. The results suggest in addition to body weight, adaptations related to osteophagy that increase jaw strength, bite force and dental robusticity can be important factors in affecting tooth-mark size. Highlights: Carnivorous animals have modified and contributed to faunal assemblages in Australian archaeological sites Taphonomic research seeks to identify carnivores that have modified faunal remains by comparing size of tooth-marks made on bone Experimental feeding trials were conducted to determine the difference in the size of tooth-marks from Australian carnivores Tooth-marks displayed large similarities in size across several body weight classes, making differentiation difficult Body size does not accurately predict Australian carnivore tooth-mark size, due to bone-crushing adaptations in dasyurids